العلاقة بين تدريب المناظرة العلمية باللغة العربية ومهارة الكلام - Ariffaturahman, Ariffaturahman; J. Nurhawani, J. Nurhawani (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2024)
The purpose of this research is to determine the relationship between Arabic debate training and Arabic speaking skills among Dayah Jeumala Amal students who are members of the Jeumala Arabic Club (JAC), and to identify the extent of the relationship between arabic debate training and arabic speaking skills for Dayah Jeumala Amal students from Jeumala Arabic Club (JAC) members. The research method used by researchers is a quantitative method with product moment correlation type by using SPSS. The sample population is Dayah Jeumala Amal students from members of the Jeumala Arabic Club (JAC). .There is a relationship between Arabic debate training and speaking skills with measurements (rcount>rttable), according to the research's findings, which were obtained using questionnaires and documentation. The correlational analysis between JAC members at Dayah Jeumala Amal indicates that the relationship between Arabic debate training and speaking skills is average, or normal.